1982
DOI: 10.1128/aac.22.4.701
|View full text |Cite
|
Sign up to set email alerts
|

Transferable resistance to cefoxitin in Bacteroides thetaiotaomicron

Abstract: Cefoxitin resistance, but not resistance to clindamycin, erythromycin, lincomycin, or tetracycline, was transferred by a conjugation-like process from Bacteroides thetaiotaomicron UN101, a clinical isolate harboring four kinds of plasmids, to other Bacteroides species. Of a sample of 20 cefoxitin-resistant transconjugants, 8 contained all 4 plasmids, 10 contained 1 to 3 plasmids, and 2 contained no plasmids.Although the transfer of resistance to several antibiotics has recently been demonstrated in Bacteroides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…This is uncharacteristic of commonly described beta-lactamases of the B. fragilis group which inactivate cephalosporins at higher rates than penicillins and represents the acquisition of a qualitatively different resistance mechanism transfer capability (18,22). Finally, cefoxitin resistance transfer has been reported in a strain of B. thetaiotaomicron by Rashtchian et al (16). However, the mechanism of the resistance in this isolate was not determined.…”
Section: Resultsmentioning
confidence: 99%
“…This is uncharacteristic of commonly described beta-lactamases of the B. fragilis group which inactivate cephalosporins at higher rates than penicillins and represents the acquisition of a qualitatively different resistance mechanism transfer capability (18,22). Finally, cefoxitin resistance transfer has been reported in a strain of B. thetaiotaomicron by Rashtchian et al (16). However, the mechanism of the resistance in this isolate was not determined.…”
Section: Resultsmentioning
confidence: 99%
“…B. fragilis strain TAL4 170 was shown to transfer P-lactamase-mediated cefoxitin resistance to a susceptible B. fragilis recipient by conjugation [90]. Also, cefoxitin resistance transfer has been demonstrated in a strain of B. thetaiotaomicron, although the precise resistance mechanism for this isolate was not determined [91].…”
Section: P-lactamasesmentioning
confidence: 99%
“…In contrast to the transmissible Tcr and erm systems, there is no detailed information available on the genetic elements encoding transmissible 3-lactam resistance. In previous reports, plasmid-free transfer of cefoxitin (FX) resistance was observed, but there was no further characterization of the determinants responsible for transfer (6,24,26).…”
mentioning
confidence: 99%
“…In contrast to the transmissible Tcr and erm systems, there is no detailed information available on the genetic elements encoding transmissible 3-lactam resistance. In previous reports, plasmid-free transfer of cefoxitin (FX) resistance was observed, but there was no further characterization of the determinants responsible for transfer (6,24,26).Recently, we described the cloning and nucleotide sequence analysis of a novel, widely disseminated P-lactamase gene (cfr4) encoding Fxr in Bacteroides species (21). This resistance gene is not plasmid encoded, but preliminary evidence showed that the resistance phenotype was transmissible when donor cells were grown in the presence of TC 2682…”
mentioning
confidence: 99%